Stigma Toward People Living with HIV/AIDS: Nursing Students’ Perspectives as Preparation for Long-Term Care - I Nyoman Arya Maha Sri Putra; I Nengah Adiana; I Wayan Edi Sanjana; Ni Putu Sri Haryati (GLOBAL HEALTH SCIENCE GROUP, 2024)
As of 2022, an estimated 39 million people were living with HIV (PLHIV) globally, with approximately two-thirds—or 25.6 million—residing in the African region. In the same year, HIV was responsible for approximately 630,000 deaths worldwide. Individuals living with HIV are particularly susceptible to stigma, which can adversely affect their quality of life. HIV-related stigma has been shown to significantly impact the health outcomes, daily lives, and overall well-being of PLHIV, particularly within key populations. Objective: This study aims to examine nursing students' perceptions of HIV-related stigma. Method: This type of research is a qualitative research with narrative design. In-depth interviews was data collection techniques with informants determined by purposive sampling technique with a total of 8 Nursing Students. The research instrument is the researcher himself and the collection of data through interviews and documentation. The data were analyzed using thematic analysis, which involved reviewing the transcripts and categorizing the data into themes. The next step involved coding, where labels were assigned to each relevant piece of information. Results: Through interviews, four main themes emerged, illustrating students' attitudes, challenges, and readiness in engaging with people living with HIV/AIDS (PLWHA) Conclusions: Despite possessing adequate knowledge regarding HIV/AIDS transmission, nursing students' perceptions in providing care for PLWHA remain influenced by prevailing social stigma.